2015
DOI: 10.1111/nph.13276
|View full text |Cite
|
Sign up to set email alerts
|

A hemicellulose‐bound form of silicon inhibits cadmium ion uptake in rice (Oryza sativa) cells

Abstract: Summary Silicon (Si) alleviates cadmium (Cd) toxicity in rice (Oryza sativa). However, the chemical mechanisms at the single‐cell level are poorly understood. Here, a suspension of rice cells exposed to Cd and/or Si treatments was investigated using a combination of plant cell nutritional, molecular biological, and physical techniques including in situ noninvasive microtest technology (NMT), polymerase chain reaction (PCR), inductively coupled plasma mass spectroscopy (ICP‐MS), and atomic force microscopy (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(91 citation statements)
references
References 78 publications
4
87
0
Order By: Relevance
“…Nwugo and Huerta (2011) identified 60 protein spots that were differentially regulated due to Cd and/or Si treatments. The major studies that have been conducted so far focus on the Si-regulated expression level of genes responsible for metal transporters under heavy-metal stress (Kim et al 2014;Bokor et al 2014;Ma et al 2015). Further studies to determine the effect of Si-induced Mn tolerance in rice, the sequential influence of Si on gene expression, and the possible Si-gene interactions are currently being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nwugo and Huerta (2011) identified 60 protein spots that were differentially regulated due to Cd and/or Si treatments. The major studies that have been conducted so far focus on the Si-regulated expression level of genes responsible for metal transporters under heavy-metal stress (Kim et al 2014;Bokor et al 2014;Ma et al 2015). Further studies to determine the effect of Si-induced Mn tolerance in rice, the sequential influence of Si on gene expression, and the possible Si-gene interactions are currently being explored.…”
Section: Discussionmentioning
confidence: 99%
“…For example, da Cunha and do Nascimento (2009) showed simultaneous presence of silica, Cd, and Zn deposits in root mesophyll cells of maize plants and suggested Si-metal complexes in plants. Liu et al (2013a) and Ma et al, (2015) reported the co-deposition of Si and Cd in the root cell walls via a [Si-wall matrix]Cd complex formation might reduce the Cd uptake by the plants suggesting in vivo detoxification of Cd in rice. Shi et al (2005b) reported that in rice roots Si and Cd was mainly deposited in endodermis and reduced the cell wall porosity of inner root tissues and they hypothesized the co-precipitation of Si with cadmium.…”
Section: Of Silicon With Metalsmentioning
confidence: 99%
“…Nwugo and Huerta (2010) investigated the effect of Si on the leaf proteome of rice plants under Cd stress and identified 60 protein spots that were differentially regulated due to Cd and/or Si treatments. More recently, Ma et al (2015) reported that in rice plants expression of Lsi1 gene was up regulated in the presence of Si in the medium, whereas expression of natural resistance-associated macrophage protein 5 (Nramp5) gene, involved in the transport of Cd, was down-regulated. In addition, Song et al (2014) reported that Si application enhanced the expression of genes (Os08g02630 (PsbY), Os05g48630 (PsaH), Os07g37030 (PetC), Os03g57120 (PetH), Os09g26810 and Os04g38410) associated with photosynthesis in rice under Zn toxicity.…”
Section: Modification Of Gene Expressionmentioning
confidence: 99%
“…Taken together, previous studies showed that Si mainly decreased root Cd uptake and/or restricted root-to-shoot Cd translocation. Ma et al (2015) have already demonstrated, by using suspension cells of rice, that negatively charged Si-hemicellulose is formed that is able to bind Cd cations which ultimately prevents the cellular uptake of Cd. For protoplasts, Greger et al (2016) …”
Section: Introductionmentioning
confidence: 99%